Analysis of quality of care for patients who are black or poor in rural and urban settings - Kahn, Katherine L.; Pearson, Marjorie L.; Harrison, Ellen R., 1962-; Rogers, William H., 1951-; Brook, Robert H. (Robert Henry), 1943-; Desmond, Katherine; Keeler, Emmett B.; Rand/UCLA/Harvard Center for Health Care Financing Policy Research (Santa Monica, CA : RAND, 1993)
This study finds racial and financial characteristics influence the quality of care received by acutely ill, insured patients after hospital admission. The study uses a clinically detailed data set to examine a comprehensive range of services provided to patients with one of five serious, common diseases in different types of hospitals. The report examines quality of care provided to patients who are black, make use of Medicaid insurance in addition to Medicare, and live in poor neighborhoods, as compared with subsets of patients who are not black, do not have Medicaid insurance, and do not live in poor neighborhoods. It also compares quality of care for inner-city patients and rural patients with that for urban patients who are not poor.
"RAND/UCLA/Harvard Center for Health Care Financing Policy Research."
Includes bibliographical references (p. 135-139).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: African Americans -- Hospital care -- United States -- Evaluation; African Americans -- Medical care -- United States -- Evaluation; Poor -- Hospital care -- United States -- Evaluation; Poor -- Medical care -- United States -- Evaluation; Rural hospitals -- United States -- Evaluation